Razvoj škržnih (branhialnih) organov - Petrovič, Danijel (Medicinski razgledi, 2002)
The branchial or pharyngeal apparatus is the region extending from the oropharyngeal (buccopharyngeal) membrane to the trachea. This apparatus consists of the branchial (pharyngeal) arches, the pharyngeal pouches, the branchial (pharyngeal) grooves and the branchial membranes. In the 4th and 5thweek of the development of the embryo five pharyngeal pouches, four branchial grooves and five branchial arches are seen in the branchial apparatus. Several structures of the head and neck, the thyroid gland, the thymus, part of the pituitary gland and the larynx are formed from the branchial apparatus.
Keywords: Branchial region; Žleze slinavke; Tongue; Jezik; Language; Obraz; Embryology; Škržni loki; Salivary glands; Ščitnica; Thyroid gland; Face; Hipofiza; Pituitary gland; embriologija; histologija; škržno črevo; razvoj